Short Communication: A comparison of stand structure, species diversity and aboveground biomass between natural and planted mangroves in Sikka, East Nusa Tenggara, Indonesia - Jeriels Matatula; Ahmad Yusuf Afandi; Pandu Wirabuana (Society for Indonesian Biodiversity, 2021)
Abstract. Matatula J, Afandi AY, Wirabuana PYAP. 2021. Short Communication: A comparison of stand structure, species diversity and aboveground biomass between natural and planted mangroves in Sikka, East Nusa Tenggara, Indonesia. Biodiversitas 22: 1098-1103.  The effectiveness of mangroves reforestation can be evaluated by comparing the stand dynamics of planted mangroves with natural mangroves in similar site conditions. This study investigated stand structure, species diversity and aboveground biomass between natural and planted mangroves in Sikka, East Nusa Tenggara. A field survey was conducted using quadrat transect method for vegetation measurement, especially related to species composition and its size distribution. Several parameters were recorded in field observation, including number of species, diameter, height, volume, and aboveground biomass. The stand structure of both mangroves was demonstrated by the distribution of diameter class while the species diversity was described using three parameters, i.e., richness, heterogeneity, and evenness. Moreover, the IVI of each species recorded was also calculated to understand the contribution of species in the mangrove ecosystems. The comparison of stand characteristics between natural and planted mangroves was examined by Mann-Whitney test and Spearman Correlation was also applied to understand the relationship between IVI and aboveground biomass. The results showed that the diameter and height between the natural and planted mangroves significantly differed (P<0.05). In contrast, there was no significant difference in tree density, volume, and aboveground biomass (P<0.05). The stand structure of both mangrove stands followed the pattern of J-inverse in which the frequency of trees decreased with the increase in diameter class. Species diversity in both stands was statistically equal in richness, heterogeneity, and evenness (P>0.05) even though there were some specific species which only observed in the natural or planted mangroves. The most superior species in the planted mangroves was Rhizophora mucronata (IVI = 96.99) while the most important plant in the natural mangroves was Sonneratia alba (IVI = 82.49). Our study found there was a significant correlation between IVI and aboveground biomass in which species with higher IVI indicated greater aboveground biomass. Based on these findings, restoration efforts of degraded mangroves in Sikka have been effective. The restoration, which has been conducted for almost three decades, has not only brought back its vegetation cover but also the functional traits of the mangrove stand to mimic with natural mangroves in the area.